The Kumon Method: Its Importance in the Improvement on the Teaching and Learning of Mathematics from the First Levels of Early Childhood and Primary Education - Orcos, Lara; Hernández-Carrera, Rafael M.; Espigares Pinazo, Manuel Jesús; Magreñán, Á. Alberto (Mathematics, 2019)
The present work gathers an educational experience based on the application of the personalized Kumon Mathematics Method, carried out in the school year 2015-2016, in which 30,849 students and 230 teachers from several educational centers throughout Spain have participated. We start with a theoretical foundation of the Kumon Method and continue with a description of the research methodology used. The empirical analysis carried out has been both in descriptive and correlational terms, using Spearman's Rho statistic, between the levels at which the students of the sample have started and the Kumon level reached. The results show that the sooner students begin to learn Mathematics with the Kumon Method, the greater the chance of reaching a level of knowledge above their school level, which helps us to demonstrate the potential of this method in the teaching and learning process of Mathematics in the educational levels of Early Childhood and Primary Education.
Keywords: Kumon Method; personalized education; mathematics learning process; spearman's rho; Early Childhood and Primary Education; JCR; Scopus